2021
DOI: 10.4103/2311-8571.328617
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Autoimmune Encephalomyelitis Inhibited by Huangqi Guizhi Wuwu Decoction via Th2 Cytokine Enhancement

Abstract: Background: Huangqi Guizhi Wuwu decoction (HQGZWW) exhibits good effects when administered to treat multiple sclerosis (MS) and its animal model, experimental autoimmune encephalomyelitis (EAE). Understanding the precise mechanism of this decoction is thus important. Based on the findings of our previous study, the aim of the present study was to understand the role of antigen-specific CD8+ T-cells on the pathogenesis of MS/EAE when HQGZWW is administered as treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 23 publications
5
21
0
Order By: Relevance
“…Pyroptosis, a specific type of programmed cell death, comes into play when the integrity of the cell membrane is compromised, leading to the release of inflammatory substances. This process is activated in response to either pathogenic infections or the stimulation of danger signals 22,23 . Pyroptosis hinges on the development of the NLRP3 inflammatory complex, which initiates an inflammatory cascade resulting in the secretion and release of IL‐1 and IL‐18.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis, a specific type of programmed cell death, comes into play when the integrity of the cell membrane is compromised, leading to the release of inflammatory substances. This process is activated in response to either pathogenic infections or the stimulation of danger signals 22,23 . Pyroptosis hinges on the development of the NLRP3 inflammatory complex, which initiates an inflammatory cascade resulting in the secretion and release of IL‐1 and IL‐18.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed when implanting a vancomycin-loaded calcium phosphate-calcium sulfate composite in rats with infection, in which new bone formation as well as the inhibition of bacterial growth occurred ( Boyle et al, 2019 ). In addition, vancomycin-loaded HAp has been shown to effectively treat chronic osteomyelitis in a rabbit model after treatment for three or 4 weeks ( Shirtliff et al, 2002 ; Joosten et al, 2004 ; Peng et al, 2021 ). Therefore, whether vancomycin-loaded Bicera™ can treat or even prevent infection in vivo requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The cell suspensions were prepared in 0.2 mL of phosphate-buffered saline, as described previously. 4,5,54 2.9 | Histological study Spinal cord sections were prepared from tissues collected from tEAE animals. 4,5,54 Spinal cord tissues were fixed in 4% ice-cold paraformaldehyde/methanol solution and embedded in paraffin before being sectioned (5-mm-thick) using a microtome for staining with hematoxylin and eosin (H&E) and Luxol fast blue (LFB).…”
Section: Adoptive-transferred Eae Models (Teae)mentioning
confidence: 99%
“…1,2 In the past few decades, MS and experimental autoimmune encephalomyelitis (EAE) have been recognized as typical CD4 + T cell-mediated autoimmune diseases. 3 Multiple studies, including our previous research, have demonstrated the involvement of CD8 + T cells in different stages of MS/EAE 4,5 and have shown that the number of CD8 + T cells is greater than that of CD4 + T cells in the brain lesion area, perivascular cuff, and white matter area. 3,6 Given their critical role in the pathogenesis of MS, CD8 + T cells may be a significant target for MS/EAE treatment.…”
Section: Introductionmentioning
confidence: 96%